Perovskite solar cells: Thermal and chemical stability improvement, and economic analysis. (January 2023) - Ahmed, Shams Forruque; Islam, Nafisa; Kumar, P. Senthil; Hoang, Anh Tuan; Mofijur, M.; Inayat, Abrar; Shafiullah, G.M.; Vo, Dai-Viet N.; Badruddin, Irfan Anjum; Kamangar, Sarfaraz
Abstract: Perovskite solar cells (PSCs) are highly efficient and are comparatively cheaper than the large silicon crystals primarily used in solar cells. Their outstanding photovoltaic performance makes them a potential alternative to silicon solar cells. While efficiency and photovoltaic performance have been investigated in recent decades, a knowledge gap on the degradation, economic feasibility and stability of PSCs exists, and their poor stability remains a barrier to commercialization. Thus, this review aims to fill this knowledge gap by focusing on approaches to improve PSCs' thermal and chemical stability, and their economic viability under different conditions. The structure and manufacture of PSCs are also discussed along with an economic analysis of different perovskite devices. Improvements in thermal stability can be reached by incorporating inorganic materials into the PSC. A PSC model optimized with ZnO improves chemical stability by 8% and works well under low temperatures. To make PSCs more economically feasible, certain parts like counter electrodes (CE) and hole transport materials (HTMs) can be replaced with alternative elements like carbon and inorganic HTMs, respectively. PSCs with long durability and high conversion efficiency will expand the commercial prospects for this material. To bridge the lack of knowledge, further investigation is required on the sustainability and longevity of PSCs. Highlights: Strategies to improve PSCs' thermal and chemical stability, and their economic viability are reviewed. A ZnO-optimized PSC model improves chemical stability by 8% and works well at low temperatures. The caffeine-based PVSK system is found thermally stable for over 1300 h at 85 °C. The optimal crystal structure of perovskite can cost 0.1784/g. To make PSCs economically feasible, CE and HTMs can be replaced by carbon and inorganic HTMs.